ANALISIS PENGENDALIAN KUALITAS PRODUK ROTI MANIS MENGGUNAKAN METODE SIX SIGMA (Studi Kasus pada UMKM Mahkota Bakery di Malang) - Mahardika, Nidya Shara; Saputri, Luluk; Amilia, Winda; Wiyono, Andi Eko (Jurnal Penelitian Sains dan Teknologi Indonesia, 2025)
A Mahkota Bakery is one of the UMKM engaged in the food sector which was established in 2012 and is located at Jalan Parangargo No. 27, Wagir District, Malang Regency. Some of the products produced include white bread, sweet bread, tarts, and donuts. The problem that often occurs is product defects, especially in sweet bread, namely extrusion defects and burnt bread. The study aims to determine the factors causing defects in sweet bread products and also provide recommendations for quality improvement proposals for sweet bread products. The method used in this study is the six sigma method using DMAIC. The results obtained from this method are in the Pareto diagram to determine the number of defects, namely extrusion defects of 2,105 pcs with a percentage of 59% and also burnt bread of 1,454 pcs with a percentage of 41%. Then determine the cause of the defects and formulate recommendations for improvements, namely the creation of SOP related to specific task divisions, installation of SOP boards, and implementation of SOP. Periodic checks during the baking process and equipment upgrades such as ovens and automatic cake fillers. Keywords: Quality, Defects, Six Sigma, DMAIC